THE POWER OF FYP: TIKTOK’S IMPACT ON ENGLISH LANGUAGE EXPOSURE AMONG GENERATION Z WITHIN PESANTREN ENVIRONMENT - Pynkan Kartike Putri; Fadhilah Ramadhani; Dwi Wara Wahyuningrum; Zeny Luthvia; Ervin Yudianto; Faiz Rizki Muhammad (Institut Agama Islam Negeri Bone, 2026)
In the digital era, digital platforms have significantly transformed the learning landscape, particularly for Generation Z, including those within the Pesantren sphere, a generation that has grown alongside digital technology despite years of boarding school life. Among these platforms, TikTok stands out as one of the most influential, especially in shaping language acquisition by introducing new vocabulary, idioms, and grammatical structures, thereby impacting the evolution of English. This study examines English-language TikTok content, focusing on the widely used For You Page (FYP) tag, to explore its influence on both language trends and learners. Employing a descriptive qualitative approach, the research highlights Gen Z users' experiences through open-ended questionnaires and interviews, while thematic analysis is applied to interpret their stories. The findings reveal that TikTok contributes to noticeable changes in English, particularly in vocabulary and structures. Moreover, this study provides insights into how future generations may adapt to these linguistic shifts through this research of TikTok’s perceived impact on language learning.